Effects of steel fibers on the dynamic properties and failure process of ultra-high performance concrete. (15th December 2022) - Yang, Shanglin; Tang, Ziqi; Zhong, Wei; Wang, Shufei; Zhang, Run; Yao, Xiaohu
Abstract: In the building area, an increasing number of applications have been made of ultra-high performance concrete (UHPC) because of its excellent properties. The steel fiber, as one of the popular admixtures of UHPC, can have a significant impact on the properties and failure process of UHPC under dynamic loading. A series of dynamic compression and Brazilian split tests were performed on UHPC specimens with six steel fiber contents based on the split Hopkinson pressure bar (SHPB) to investigate the effects of varying fiber content on the dynamic performance of UHPC. The digital image correlation (DIC) system equipped with a high-speed camera was incorporated to assist an in-depth knowledge of the UHPC failure process. Diverse experimental results were obtained and demonstrated that the presence of steel fibers can enhance the strength and toughness of UHPC, but the crack resistance of UHPC was unremarkable when the steel fiber content was 0.5%. Over the studied range, an increase in tensile strain rate of 10 s −1 resulted in a 36% growth of tensile dynamic increase factor (DIFt ) and the variation of fiber content had little effect on the growth ratio of DIFt . While with a 100 s −1 increase in compressive strain rate, the compressive dynamic increase factor (DIFc ) increased within 27% and higher fiber content decreased this value obviously. Based on the test data, logarithmic models for compressive and tensile dynamic increase factors were proposed in which the effects of strain rate and fiber content were both incorporated. DIC analysis revealed that the inclusion of steel fibers allowed for a larger peak strain of the specimen and slower macro-crack evolution after cracking. This research facilitates further understanding of the dynamic behaviors and damage mechanisms of UHPC. Highlights: The effects of steel fiber on dynamic behaviors of UHPC and corresponding mechanisms were analyzed. DIF models incorporating the effects of strain rate and fiber content were proposed. The crack evolution was explored in terms of strain field and the cracking speed was evaluated. Addition of steel fibers allowed for greater deformation before failure and arrested the macro-crack expansion after failure.